El precio de las palabras: salarios y contratos de sofistas y maestros en los documentos papiráceos - Gonzàlez Julià, Lluís (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2010)
This paper aims to explore two features of the activity of sophists and teachers which, to date, have not been studied enough because of the lack of suffi cient evidence conserved in the papyri. However, a comparison between these documents and the information given in literary texts allows us to imagine the true fees of teachers and sophists, as well as how their services were contracted.
Keywords: Sophists; Teachers; Fees; Contracts; Papyri